Pengaruh Karakteristik Perusahaan Terhadap Nilai Perusahaan Dengan Intellectual Capital Sebagai Variabel Moderasi - Achyani, Fatchan; Trisnawati, Rina; Mulato, Febry Yuni (IAIN Surakarta, 2020)
This study aims to analyze the effect of company characteristic on company value with intellectual capital as a moderating variable. In this study, the independent variable is the company, namely liquidity, profitability, capital structure, and size, while the dependent variable is company performance, which is the firm's value. Liquidity variables are accepted by the Current Ratio, profitability variables are collected by Return of Assets (ROA), capital structure is accepted by debt to equity (DER), and size is measured by Ln (Total assets). Company value variables are valued by Torbin Q, and intellectual capital is obtained by Intellectual Coefficient Add Value as a moderating variable. The sample in this study was obtained using a purposive sampling of 36 manufacturing companies received on the Indonesia Stock Exchange in 2015-2017. The results of this study indicate that (1) liquidity has a significant effect on firm value, (2) profitability has no effect on firm value, (3) capital structure has a significant effect on firm value , (4) size has no effect on firm value, (5) intellectual capital is able to moderate the relationship of liquidity and capital structure to firm value. (6) Intellectual capital is not capable of moderate the relationship of profitability and size to firm value.Keywords: Firm Value, Intellectual Capital, Liquidity, Profitability, Capital Structure and Firm SizeJEL Classification Codes: L25, L60, M41,O34